bottleneck acts as a regulator of the microfilament network governing cellularization of the Drosophila embryo. - Schejter, E.D.; Wieschaus, E. (Cell, 1993)
A dynamic network of cortical microfilaments is associated with the cleavage furrow membranes during cellularization of the Drosophila embryo. A specific set of structural rearrangements in this network is required for orchestration and execution of its mechanistic roles. We describe the characterization of the gene bottleneck (bnk), mutations in which disturb the proper sequence of rearrangements of the microfilament network, leading to a variety of morphological defects during cellularization. bnk, whose expression is restricted to the blastoderm stages of Drosophila embryogenesis, encodes a novel, exceptionally basic protein that specifically colocalizes with the microfilament network. The expression pattern and mutant phenotype of bnk suggest a direct role for this element in regulation of the dynamic restructuring of the actin-based cytoskeleton of cellularizing Drosophila embryos.